Recent Developments in SPECT/CT - Ritt, Philipp (Seminars in Nuclear Medicine, 2022)
The debut of multimodal Single Photon Emission Computed Tomography/X-ray Computed Tomography (SPECT/CT) has signified an important advancement of Nuclear Medicine imaging by allowing for high-quality attenuation correction and co-registration/fusion of metabolic and anatomical images. This progress in SPECT instrumentation continued and resulted in the clinical application of several new techniques, such as for example, semiconductive Cadmium-Zinc-Telluride (CZT) detectors, quantification of radiopharmaceutical uptake in absolute units, whole-body SPECT acquisitions with multiple bed positions, and novel non-parallel hole collimators. Many other new methods were reported from literature during the last years, but still await implementation in clinical routine. Here, examples are multipinhole collimators, iterative reconstruction with Monte-Carlo projectors, list-mode SPECT acquisitions, and quantitative imaging of alpha-emitters. For the future, it could be expected that deep-learning approaches would be applied for Nuclear Medicine imaging, confirming the promising results reported by research groups. More efforts should be made for standardizing quantitative SPECT, to allow for inter-site comparability of radiopharmaceutical uptake and derived quantities such as dosimetry results. The awaited market authorization of several SPECT-imageable therapeutic radiopharmaceuticals will drive the interest in SPECT/CT and ensure that it remains the workhorse of Nuclear Medicine.
CRIS-Team Scopus Importer:2022-03-18